LEGISLATIVE SUPPORT OFADULT EDUCATION IN UKRAINE: USE OF THE EXPERIENCE OF EU EDUCATION POLICY - Sergeyeva, O. S. (Continuing Professional Education: Theory and Practice, 2019)
The article highlights the ways of overcoming shortcomings in the law provided adult education in Ukraine through showingthe gradual adoption of a number of public documents in the educational policy of the European Union in the field of adult education and lifelong education. The article demonstrates problems caused by certain gaps in contemporary educational policy according to adult education. The main trends in education policy in general and in particular adult education are common for many European countries, including Ukraine that is not an exception, as its policies in education aimed at integration into the European and world educational space. Using the experience of the educational policy of the European Union in the field of adult education is that we have a vivid example of the phased development of adult education by making public documents and the use of public leverage on the basic trends of lifelong education and adult education as one of its important components.We consider it necessary to mention three main stages in the development of adult education in the educational policy of the European Union, according to which we observed positive trend in the industry and an example for building an educational policy in the field of adult education in Ukraine: 1) (19571975 рр.);2) (19761996 рр.); 3) (19972013). It should be noted that an important trend in the development of education in Ukraine is to provide adult education legitimacy and acceptance of public documents that would ensure the human right of all ages for the profession, regardless of the status and security of people